Prevalence and factors associated with medication adherence in children with central precocious puberty: a cross-sectional study - Yang, Chunsong; Song, Xia; Wu, Jin; Zhang, Lingli (Frontiers in Pharmacology, 2024)
Objectives: This study aimed to investigate the prevalence and influencing factors of medication adherence in children with central precocious puberty (CPP), and provide references for clinical practice.Children under 12 years of age with CPP and their caregivers at a women's and children's hospital were selected for a cross-sectional study from February to May 2023, and a questionnaire was used to collect basic characteristics of pediatric patients and their caregivers, information of medication, cognition of medication, and medication adherence.The 8-item Morisky Medication Adherence Scale (MMAS-8) was adopted to assess medication adherence, and the potential influencing factors were explored by univariate and multivariate analyses.Results: A total of 125 valid questionnaires were collected. The medication adherence rate of children with CPP reported by caregivers was 76.0%. The univariate analysis showed that the percentage of parental caregivers (P=0.027), the age of caregivers (P=0.029), the education level of caregivers (P= 0.001), the financial burden (P<0.000), the incidence of adverse effects (P=0.008), and the cognition of medication including the importance of medication (P=0.002), the dosage of medication (P=0.002), the adverse effects of medication (P=0.007), the harm of non-compliance with medication (P<0.000), and the evaluation of the price of medication (P=0.003) in the poor adherence group were significantly inferior to those in the better adherence group. The multivariate analysis showed that the higher incidence of adverse effects (P=0.20), not understanding the harm of non-compliance with medication (P=0.004), and evaluation of the price of medication as expensive (P=0.043) were independent risk factors for poor medication adherence.Conclusions: Medication adherence in children with CPP is relatively better, and the factors leading to poor medication adherence are mainly on the caregivers of pediatric patients. It is recommended to increase the health education among caregivers of children with CPP to enhance the cognition of the condition and medication, and further improve the therapeutic efficacy for CPP.